2016
DOI: 10.1248/cpb.c16-0429
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis and Evaluation of Arctigenin Amino Acid Ester Derivatives

Abstract: The use of arctigenin (ARG), a traditional medicine with many pharmacological activities, has been restricted due to its poor solubility in water. Five amino acid derivatives of ARG have been synthesized using glycine, o-alanine, valine, leucine, and isoleucine, which have t-butyloxy carbonyl (BOC) as a protective group. In this study, we examined the effects of removing these protective groups. The results showed that the amino acid derivatives have better solubility and nitrite-clearing ability than ARG. Amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…After introducing different amino acids in the 3-hydroxyl of OA using the ester condensation reaction, the ClogP of the derivatives reduced to a certain degree, which of glycine, alanine, and lysine conjugates was most significant. It was also in line with the theory of drug design and our previous reports, as well as others [ 22 , 23 , 24 , 25 ]. More importantly, most of the derivatives had some alkalinity with different cell inhibitory activities.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…After introducing different amino acids in the 3-hydroxyl of OA using the ester condensation reaction, the ClogP of the derivatives reduced to a certain degree, which of glycine, alanine, and lysine conjugates was most significant. It was also in line with the theory of drug design and our previous reports, as well as others [ 22 , 23 , 24 , 25 ]. More importantly, most of the derivatives had some alkalinity with different cell inhibitory activities.…”
Section: Discussionsupporting
confidence: 92%
“…Amino acids are the most basic material composed of proteins in organisms and related to life activities. When amino acids or peptides were introduced into the structure of the active ingredients from traditional Chinese medicine, it could improve the hydrophilicity, increase the bioactivity, and mitigate the adverse reaction significantly [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. In our previous study, different polarity amino acids or dipeptides were introduced into 3-hydroxyl o Oleanolic acid-ligustrazine derivative (TOA) and Betulinic acid-ligustrazine derivative (TBA), the anticancer lead compound [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in our laboratory have shown that ARG-V has better solubility and nitrite removal activity than ARG 28 . On this basis, their pharmacological activities and their impact on immune function were compared in H 22 tumour-bearing mice.…”
Section: Introductionmentioning
confidence: 81%
“…Our team has studied the nitrate scavenging activity of ARG and ARG-V using diazo coupling spectrophotometric method 28 .…”
Section: Methodsmentioning
confidence: 99%
“…Cai et al ( 2016 ) synthesized a series of ARG amino acid derivatives, all of which have better solubility and nitrite elimination ability than those of ARG. This compound and its two amino acid derivatives without a Boc protection group ( 22 , 23 ) were selected for in vivo antitumor activity evaluation.…”
Section: Application Of Amino Acids In the Structural Modification Of Natural Productsmentioning
confidence: 99%